Foreword - PEDESTRU, Mihai (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
From the Nāṭyaśāstra or Aristotle’s Poetics to social media posts or the new online review aggregators, discourses about theater have shaped the course of the art’s evolution, reflecting and influencing aesthetics, modes of production and models of social and political involvement.